If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(2f + -3) = 4(f + -8) Reorder the terms: 8 + -1(-3 + 2f) = 4(f + -8) 8 + (-3 * -1 + 2f * -1) = 4(f + -8) 8 + (3 + -2f) = 4(f + -8) Combine like terms: 8 + 3 = 11 11 + -2f = 4(f + -8) Reorder the terms: 11 + -2f = 4(-8 + f) 11 + -2f = (-8 * 4 + f * 4) 11 + -2f = (-32 + 4f) Solving 11 + -2f = -32 + 4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4f' to each side of the equation. 11 + -2f + -4f = -32 + 4f + -4f Combine like terms: -2f + -4f = -6f 11 + -6f = -32 + 4f + -4f Combine like terms: 4f + -4f = 0 11 + -6f = -32 + 0 11 + -6f = -32 Add '-11' to each side of the equation. 11 + -11 + -6f = -32 + -11 Combine like terms: 11 + -11 = 0 0 + -6f = -32 + -11 -6f = -32 + -11 Combine like terms: -32 + -11 = -43 -6f = -43 Divide each side by '-6'. f = 7.166666667 Simplifying f = 7.166666667
| 5x+100=0 | | 2k-10=-7 | | [7x+20]=[8x-5] | | x-10=-3x | | 20+k/19=10 | | -3.2x-1.4x=-9.2 | | tg(2x)=-7.57 | | x=12.5+-1.5y | | -2p+p= | | 6/7y-11=28 | | g^2+2gh+h^2= | | -10n-10+2n-5= | | 2x^2+6-5=0 | | x-14.50=53.00 | | -6+7x=-20 | | y-y+8y-3=11+y | | 6t^3-2t^2-14t+8=0 | | 16x^2+11x-5= | | 11x+4x= | | 16x^2-79x-5= | | T+6/t=7t/5t | | 5/u-8=7 | | -15a-22=14 | | 9x+4(12-x)= | | 5-x/6=9 | | 4-3.5x=12 | | y-3.25=8 | | 300/180*100= | | 3(7)+9=30 | | 5m-3n+2m-m= | | 300/180= | | 1200a+45-1800a+60= |